Performing Art of Uzbek Status (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article talks about the history, development and current level of Uzbek status performance art. Among them, it is said that the art of status is an intangible cultural heritage of the Uzbek people, the melody that has leaked from the body of our people, and that we, the youth, should preserve this heritage, the melody, and pass it on to our future generations.